Aeroallergen Sensitization in Asthmatics children and its association with Asthma severity - Ajay Kosam; Durga Kosam (International Journal of Medical Research and Review, 2015)
Introduction: Chronic low level exposure and sensitization to indoor allergens plays a major role in asthma pathogenesis and subsequent provocation of symptoms. Asthma severity is proportional to degree of aeroallergen exposure and sensitization. This study was conducted to determine the prevalence of sensitization to common aeroallergens and its association with asthma severity.Material and methods: Cross sectional observational study that evaluated 70 asthmatic patients from 5 – 18 years of age attending pediatric allergy asthma clinic at a tertiary care teaching hospital from January to December 2014. Skin prick test was performed on all these patients. Pattern of aeroallergen sensitization and its impact on asthma severity was studied.Results: Skin prick testing (SPT) was performed on 70 children above 5 years of age, with a mean (SD) age of 8.8 (2.99) years. 52 children (74%) were sensitized to at least one aeroallergen, suggesting atopy; 27(38.5%) were sensitized to more than one allergen. 65.3% children were sensitized to house dust mite; 46.1% to alternaria, 38.4% to cynodon and 19.2% to cockroach antigens. Frequency of aeroallergen sensitization correlated with increasing age. Asthma severity was associated with sensitization to house dust mite and cockroach.Conclusion: Approximately three fourth of asthmatic children in our study were sensitized to at least one aeroallergen showing that these children had atopic/ aeroallergen induced asthma. Sensitization was most commonly seen to dust mite, alternaria and cynodon. Children sensitized to dust mite and cockroach had more severe asthma.